2003
DOI: 10.1042/bj20021603
|View full text |Cite
|
Sign up to set email alerts
|

A newly established in vitro culture using transgenic Drosophila reveals functional coupling between the phospholipase A2-generated fatty acid cascade and lipopolysaccharide-dependent activation of the immune deficiency (imd) pathway in insect immunity

Abstract: Innate immunity is the first line of defence against infectious micro-organisms, and the basic mechanisms of pathogen recognition and response activation are evolutionarily conserved. In mammals, the innate immune response in combination with antigen-specific recognition is required for the activation of adaptive immunity. Therefore, innate immunity is a pharmaceutical target for the development of immune regulators. Here, for the purpose of pharmaceutical screening, we established an in vitro culture based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 33 publications
3
62
0
2
Order By: Relevance
“…This idea is consistent with the reported link in the dipteran Drosophila melanogaster between eicosanoid biosynthesis and the immune deficiency (IMD) pathway signaling system, one of the signaling pathways responsible for induction of AMP expression (19). However, since X. nematophila inhibits the expression of genes encoding AMPs in lepidopterans (3,4,20) but not D. melanogaster insects (21,22), it appears that X. nematophila targets a step in AMP induction that is present in Lepidoptera but not D. melanogaster.…”
supporting
confidence: 78%
“…This idea is consistent with the reported link in the dipteran Drosophila melanogaster between eicosanoid biosynthesis and the immune deficiency (IMD) pathway signaling system, one of the signaling pathways responsible for induction of AMP expression (19). However, since X. nematophila inhibits the expression of genes encoding AMPs in lepidopterans (3,4,20) but not D. melanogaster insects (21,22), it appears that X. nematophila targets a step in AMP induction that is present in Lepidoptera but not D. melanogaster.…”
supporting
confidence: 78%
“…Little is known about the molecular mechanisms of action of dexamethasone in insects. Previous studies demonstrated that the immunosuppressive effect of dexamethasone in cellular immunity of insects depended on inhibition of phospholipase A 2 (PLA 2 ) and was reversed by administration of arachidonic acid (23,24,43). Nonetheless, similar to mammals, it is plausible that corticosteroids act by inhibiting multiple pathways of insect innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the genes for these two proteins was induced by injecting the eicosanoid-precursor AA into silkworm larvae. With respect to a Drosophila model, Yajima et al (2003) showed that LPS-stimulated induction of the gene encoding the anti-bacterial protein, Diptericin, is mediated by the immunedeficiency (imd) pathway, but not by the Toll pathway. In a screen of inhibitory compounds, they also found that inhibitors of PLA 2 , including p-bromo-phenacyl bromide and dexamethasone, repressed LPS-stimulated gene expression.…”
Section: Introductionmentioning
confidence: 99%